Pengaruh Model Role Playing dalam Pembelajaran Tematik terhadap Hasil Belajar Siswa Kelas V Sekolah Dasar Negeri 34 Pontianak Selatan - Lira Aurika; Siti Halidjah; Rio Pranata (Departement of Mathematics Education, 2024)
This research aims to analyze the influence of the role playing model in thematic learning on the learning outcomes of class V students at SD Negeri 34 South Pontianak by conducting experimental research in the form of a Nonequivalent Control Group. The research sample consisted of 35 class A students (experimental class) and 34 class C students (control class) at SD Negeri 34 South Pontianak. Data collection techniques use measurement techniques with instruments in the form of essay questions. The results of the pre-test and post-test calculations for the experimental class were 23.08 and 84.32. Meanwhile, the pre-test and post-test results for the control class were 26.77 and 72.65. Based on calculations using the N-Gain formula, it is known that the average learning outcome in the experimental class is 0.7947 and in the control class it is 0.6395, so it is concluded that the class that uses the role playing model is better than the class that does not use the role playing model.